Short-Term Supplementation With Fermented Red Clover Extract Reduces Vascular Inflammation in Early Post-menopausal Women - Wickham, Kate A.; Nørregaard, Line B.; Oxfeldt, Mikkel; Cheung, Stephen S.; Gliemann, Lasse; Hansen, Mette; Hellsten, Ylva (Frontiers in Cardiovascular Medicine, 2022)
The decline in oestrogen at menopause poses a critical challenge to cardiovascular and metabolic health. Recently, a growing interest in the role of phytoestrogens, with a particular focus on isoflavones, has emerged as they can bind to estrogen receptors and may mimic the roles of endogenous oestrogen. Fermented red clover extract (RC) contains isoflavones with superior bioavailability compared to non-fermented isoflavones, however little is known regarding the impact of isoflavones on cardiovascular and metabolic health. We assessed markers of vascular health in plasma and skeletal muscle samples obtained from healthy but sedentary early post-menopausal women (n = 10; 54 ± 4 yrs) following two weeks of twice daily treatment with placebo (PLA) or RC (60 mg isoflavones per day). The two interventions were administered using a randomized, double-blind, crossover design with a two-week washout period. Plasma samples were utilized for assessment of markers of vascular inflammation. There was a statistically significant reduction ( 5.4%) in vascular cell adhesion molecule 1 (VCAM-1) following two weeks of RC supplementation compared to PLA (p = 0.03). In contrast, there was no effect of RC supplementation compared to PLA on skeletal muscle oestrogen receptor content and enzymes related to vascular function, and angiogenesis. Supplementation with RC reduces vascular inflammation in early post-menopausal women and future studies should address the long-term impact of daily supplementation with RC after menopause.